Անհատի ողբերգության թեման Յ. Վ. Գյոթեի ստեղծագործությունների համապատկերում - Ստեփանյան, Ս.
В статье обсуждается концепция личной трагедии в произведениях Гете. Его основной целью является показать свободу воли героев в своих действиях. Развитие этой концепции тесно связано с историческими, социальными, политическими, философскими и другими факторами. С другой стороны, Гете достигает своей цели через призму своего собственного опыта. The article is devoted to the analysis of the concept of personal tragedy in all works of Goethe His main goal was to show the epitome of characters' free will through their actions.The development of this concept is closely connected with historical, social, political, phylosophical and other factors. On the other hand, Goethe realizes his aim through the prism of his real experiences.
Keywords: Գրականություն